Characterization of velvet worm slime protein - Lee, Jung Tou (Nanyang Technological University, 2023)
Velvet worms (Onychophora) eject a fluid slime to ensnare their prey. Upon ejection, the fluid dries quickly to form polymer fibers. These fibers are glassy and extremely stiff. Remarkably, these fibers are dissolvable in water, and newly regenerated fibers can be drawn from the solutions. However, the physicochemical mechanism of slime transition from liquid-to-solid is still not well understood. This project involves the rheology of crude slime and redissolved slime solutions. Both samples were observed using optical microscopy and fluorescence microscopy for signs of liquid-liquid phase separation. Rheological experiments, such as amplitude sweep and frequency sweep, were conducted to understand the slime’s rheological characteristics such as the linear viscoelastic range. Understanding these properties would give a better insight into the mechanics of the slime fibers formation